Angioneurotic oedema and urticaria following hydrocortisone–a further case. Issue 656 (June 1980) - Ashford, R. F.; Bailey, A.
Abstract : It is still not commonly realized that immediate hypersensitivity reactions to hydrocortisone can occur. A rare case is reported which illustrates the need for caution when using this drug in atopic subjects. Ideally, parenteral hydrocortisone should only be used where facilities for resuscitation are available.